2010
DOI: 10.1016/j.yhbeh.2010.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous activity, economy of activity, and resistance to diet-induced obesity in rats bred for high intrinsic aerobic capacity

Abstract: Though obesity is common, some people remain resistant to weight gain even in an obesogenic environment. The propensity to remain lean may be partly associated with high endurance capacity along with high spontaneous physical activity and the energy expenditure of activity, called non-exercise activity thermogenesis (NEAT). Previous studies have shown that highcapacity running rats (HCR) are lean compared to low-capacity runners (LCR), which are susceptible to cardiovascular disease and metabolic syndrome. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
110
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 90 publications
(125 citation statements)
references
References 75 publications
15
110
0
Order By: Relevance
“…Taken together, our results are consistent with previous data on rodents 15,25,26 and humans 27,28 , which indicated that genetic predisposition plays a significant role in exercise participation. These results are also consistent with our previous suggestion 14 that genetic pleiotropy may partly explain the associations observed between high physical activity and mortality in our past epidemiological studies, which called for high quality intervention studies to analyse the true effects of physical activity on morbidity and mortality among initially healthy individuals.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Taken together, our results are consistent with previous data on rodents 15,25,26 and humans 27,28 , which indicated that genetic predisposition plays a significant role in exercise participation. These results are also consistent with our previous suggestion 14 that genetic pleiotropy may partly explain the associations observed between high physical activity and mortality in our past epidemiological studies, which called for high quality intervention studies to analyse the true effects of physical activity on morbidity and mortality among initially healthy individuals.…”
Section: Discussionsupporting
confidence: 93%
“…Several large-scale clinical studies have shown that low exercise capacity is the strongest predictor of all-cause mortality [43][44][45]. It has been demonstrated, that in addition to a variety of biochemical and physiological differences, LCRs have significantly shorter lifespan compared to HCRs [26]. Aging is also associated with a decline in the rate of force development, especially during fast contractions [46,47].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations